A survey of educational games as interaction design tools for affective learning: Thematic analysis taxonomy - Yusoff, Zarwina; Kamsin, Amirrudin; Shamshirband, Shahaboddin; Chronopoulos, Anthony T. (Springer, 2018)
A Computer game is the new platform in generating learning experiences for educational purposes. There are many educational games that have been used as an interaction design tool in a learning environment to enhance students learning outcomes. However, research also claims that playing video games can have a negative impact on student behavior, cognition and emotion. The aim of the study is to review the related articles in educational games and the function of games as interaction design tools, which affect student’s cognition, emotion and social skills interaction when playing games. We use thematic analysis to classify the papers including the following: (a) data familiarization (b) initial code generation (c) review themes (d) themes search (e) Define & Name Themes. The articles were found from four databases: web of science, IEEE, ACM, and Springer. All the articles were analyzed based on three main research questions (1) what are the issues of survey papers in educational games? (2) What are the trends of research models in educational game? (3) What is the technology used in educational games? The results show that educational games are affective interaction design tools for learning outcomes.